An elucidation of symmetric supercapacitor with crustacean-based polymer blend electrolyte - Abd. Shukur, Muhammad Fadhlullah; Abdul Aziz, Mohd Fareezuan; Shamsuri, Nurrul Asyiqin; Hamsan, Muhamad Hafiz; Mohd Abid, Mohd Asyadi 'Azam; Mohamed Yusof, Yuhanees; Aziz, Shujahadeen B.; Rusdi, Hashlina; Abdul Kadir, Mohd Fakhrul Zamani (John Wiley and Sons Inc, 2023)
Searching for alternative materials that have biodegradable properties is one of the efforts to increase knowledge and green technology that contributes to the reduction of waste produced from electronics. A biodegradable biopolymer electrolyte system based on polyvinyl alcohol-chitosan blend is prepared using an easy and affordable method called solution cast technique. Lithium acetate (LiOAc) and ethylene carbonate (EC) are incorporated as charge carrier and plasticizing agent. The plasticization effect of EC concentrations on physical structure has been investigated and reported. The real and imaginary parts of dielectric permittivity confirmed that the highest dielectric constant and loss values are recorded at low-frequencies regions. A disruption in the crystalline region of the film can be observed with the existence of LiOAc and EC. The inclusion of EC promotes the ions dissociation thus enhanced the amorphous region of the electrolytes which is beneficial for ionic conduction. Linear sweep voltammetry analysis revealed that the highest conducting electrolyte is electrochemically stable up to 1.82 V. No redox peaks are shown in the cyclic voltammetry of the fabricated supercapacitor. The supercapacitor showed a great performance with average specific capacitance of 130 F g−1.